The Impact of Music on Pacer Test Performance, Enjoyment and Workload: 音樂對健身測試、愉快感及負荷量的影響 - DEUTSCH, Joe; HETLAND, Kristen (Asian Journal of Physical Education & Recreation, 2012)
The purpose of this study was to establish what effect music has on students PACER test performance as well as their enjoyment of the test and perceived workload. Subjects were 72 boys and girls, age 9–11. Subjects completed the 20 meter multi-stage (progressive) cardiovascular fitness test known as the Progressive Aerobic Cardiovascular Endurance Run (PACER) on three consecutive regularly scheduled class periods. At the conclusion of each test, students filled out a SelfRated Performance survey answering a number of questions about their perceived enjoyment as well as performance level. Each time the test was performed a different version was used, including a mild tempo, a higher tempo music as well as one with no music at all. Results indicated that the fewest participants regardless of gender attained their best score with the non-music version of the test [boys=8 (22%) and girls = 9 (28%]. The boys scored their highest scores on the mild tempo (n=17; 46%) while girls scored highest with the high tempo (n=13; 41%). When comparing test results to SRP scores, significant differences between each of the music versions compared to the non-music version existed (for no music versus mild, P=0.031; for no music versus faster, P=0.025). To conclude, students perform better cardiovascular when music is present. Boys perform better with milder tempo music while girls perform better on the higher tempo. Boys and girls also both enjoy the test more and perceive themselves to have worked harder when music is present as opposed when it is not.